(3cJGH aj Gdadcs - (3GdeOQfj , eMeO Hf eUWajs
(3ChdgG (B:s
(3GdMeO ddg hMOg CeG HYO ajbhd CSjQ GdeSGhi eMeO Hf eUWai gPg OjHGLI dWjaI dHjGf cjajI GdYed HGdLOhdjf GddPjf jSei CMOgeG HGdSHb hGdKGfi HGdTHcI s
(3BNQgG (B:s
(3LOhd GdMQcI ai GdYQV deYQaI ecGf GdNShajf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Hg GdYOjO ef GdLOGhds
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B36s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdadcs